Traffic capacity constraints from level 3 control transitions - Alms, Robert; Wagner, Peter (Frontiers in Future Transportation, 2025)
With the increasing integration of conditionally automated Level 3 systems into real-world traffic, concerns about their impact on traffic efficiency and capacity have emerged. When such systems reach their operational limits, mandatory control transitions could disrupt traffic flow and reduce overall capacity. This study employs large-scale simulations and numerical experiments to analyze these effects and quantify potential capacity constraints. The results of the two-lane highway scenario show an experimental capacity reduction of up to 2000 veh/h in an almost fully automated but unmanaged traffic mix, corresponding to a loss of about 60%. Control transition-related effects become increasingly pronounced at a Level 3 penetration rate between 10% and 20%. Estimated capacity reductions suggest that the maxima in time headway increments during the transition phase contribute most to these effects.